Formation of an architectural environment when creating mini-park centers - Sydygaliev D.S. Сыдыгалиев Д.С.; Amirkhanov A. Амирханов А. (Рroblems of engineering and professional education, 2022)
Parks and squares have always played an important role in the life of a city dweller. So in ancient Greece, trees and shrubs were planted on the walls of roads and large buildings. But in the cities of the Roman Empire, there was a tradition of building «sacred groves» - prototypes of modern squares. The role and significance of green spaces in today’s large cities is very difficult to overestimate. After all, they not only purify the air, but also absorb harmful substances and protect people’s homes from dust and